SUPPORTING STUDENTS' LOGICAL THINKING ABILITY WITH CASE BASED LEARNING MODEL WITH SMART QUIZ TECHNIQUE - Firdausi, Firna Nahwa; Arif, Syaiful (INSECTA: Integrative Science Education and Teaching Activity Journal, 2025)
Indonesia faces serious challenges in developing logical thinking skills, particularly in science. This skill is crucial because it serves as the foundation for students to analyze, evaluate, and create solutions to complex problems, not only in school but also in everyday life. Unfortunately, data from various sources indicates that Indonesian students' logical thinking skills are still far below global standards. The TIMSS consistently ranks Indonesia at the bottom, ranking 44th out of 49 countries with a score of 397. This study aims to 1. Determine the implementation of the CBL with the quiz technique on logical thinking skills. 2. Determine student activities during the implementation of the CBL model with the quiz technique on logical thinking skills. 3. Determine the effectiveness of the CBL with the quiz technique on logical thinking skills. This study used a quantitative approach with a quasi-experimental design. The research design involved an experimental class implementing the CBL with the quiz technique, and a control class using conventional learning methods. Data were collected after being tested for validity and reliability. The results of the study showed that the average student activity during the implementation of the CBL with the quiz technique reached 83% which is included in the good category. The results of the hypothesis test showed a significant difference in students' logical thinking abilities between the experimental class and the control class, where the sig value (2 tailed) was 0.000. The N-Gain analysis showed that the average N-Gain value of the experimental class was 0.74, which was categorized as "moderate and quite effective". Thus, this study concluded that the CBL with the quiz technique was effective in improving students' logical thinking abilities.